International Conference on Space Optics — ICSO 2018 2019
DOI: 10.1117/12.2536055
|View full text |Cite
|
Sign up to set email alerts
|

HgCdTe APDs detector developments at CEA/Leti for atmospheric lidar and free space optical communications

Abstract: HgCdTe APD detector modules telecommunication are developed at CEA/Leti for atmospheric LIDAR and free space optical (FSO). The development is driven by the design and manufacture of generic sub-assemblies that can be adapted in each detector module to meet the specific detector requirements of each application. The optimization of such subassemblies is detailed in perspective of the challenges that are set by the specifications for detector modules currently developed for atmospheric LIDAR, in the scope of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Therefore, with the typical APDs the limit would be on the order of 10 10 photon pairs per second. The suppression of the timing jitter for APDs is an area of active research and there are ongoing efforts to reduce it to tens of ps 20 .…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Therefore, with the typical APDs the limit would be on the order of 10 10 photon pairs per second. The suppression of the timing jitter for APDs is an area of active research and there are ongoing efforts to reduce it to tens of ps 20 .…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Electronics 2021, 10, x FOR PEER REVIEW 2 of 13 characteristics of the atmosphere's attenuation and the availability of sources and detectors of optical radiation [18]. The development of quantum cascade (QC) lasers operating in the long-wave infrared radiation and highly sensitive mercury cadmium telluride (MCT) detectors provided new possibilities for FSO links [19,20]. It has become possible to develop an FSO link operating at wavelengths 8-12 µ m where there is less attenuation caused by mists with fine aerosol particles than in the case of commercially available links.…”
Section: Methodsmentioning
confidence: 99%
“…It was later delivered to AIRBUS to characterize two detector modules developed by CEA/Leti. The results obtained from the first characterization (using the NIR-LEE) in AIRBUS showed that all the characterized parameters met the specifications, except the quantum efficiency to excess noise factor ratio (QEFR) and the remanence (time delay induced by a strong signal) [3]. These and other critical optical parameters will be explored in the frame of the H2020 HOLDON project [5].…”
Section: Virtual Conference 30 March-2 April 2021mentioning
confidence: 99%
“…Hence, MCT APD detectors for atmospheric lidar are being currently developed within the framework of Research and Technology National Centre for Space Studies (R&T CNES) projects and a H2020 project called HOLDON. The objective of these projects is to optimize characteristics of the MCT APD detector modules to reach the specific challenges imposed by atmospheric lidar measurements in terms of dynamic range, response time, temporal lag (remanence) and background noise [3].…”
Section: Introductionmentioning
confidence: 99%